Penerapan BCG Matrix dalam Penyusunan Strategi untuk Menghadapi Persaingan di Industri Minuman (Studi Kasus Coca Cola Company) - Daifullah, Fakhri (J-Mabes: Jurnal Manajemen, Akuntansi, Bisnis dan Studi Ekonomi Syariah, 2025)
The beverage industry is a rapidly growing sector with global revenue continuously increasing each year. Amidst intense competition, Coca-Cola Company, as one of the industry leaders, faces various challenges, such as shifting consumer preferences and growing demand for healthier products. This study aims to analyze the application of the Boston Consulting Group (BCG) Matrix in formulating corporate strategies to address these challenges. The research employs a quantitative approach with secondary data from the 2023 annual financial reports of Coca-Cola Company and PepsiCo. The analysis indicates that Coca-Cola Company is positioned in the star quadrant of the BCG Matrix, reflecting a high market growth rate and relative market share. Recommended strategies include backward integration, market development, market penetration, and product development. The implementation of these strategies is expected to help maintain Coca-Cola's competitive position in the beverage industry.